Slow protein evolutionary rates are dictated by surface–core association - Tóth-Petróczy, Ágnes (National Academy of Sciences, 2011)
Why do certain proteins evolve much slower than others? We compared not only rates per protein, but also rates per position within individual proteins. For ∼90% of proteins, the distribution of positional rates exhibits three peaks: a peak of slow evolving residues, with average log(2)[normalized rate], log(2)μ, of ca. −2, corresponding primarily to core residues; a peak of fast evolving residues (log(2)μ ∼ 0.5) largely corresponding to surface residues; and a very fast peak (log(2)μ ∼ 2) associated with disordered segments. However, a unique fraction of proteins that evolve very slowly exhibit not only a negligible fast peak, but also a peak with a log(2)μ ∼ −4, rather than the standard core peak of −2. Thus, a “freeze” of a protein's surface seems to stop core evolution as well. We also observed a much higher fraction of substitutions in potentially interacting residues than expected by chance, including substitutions in pairs of contacting surface-core residues. Overall, the data suggest that accumulation of surface substitutions enables the acceptance of substitutions in core positions. The underlying reason for slow evolution might therefore be a highly constrained surface due to protein–protein interactions or the need to prevent misfolding or aggregation. If the surface is inaccessible to substitutions, so becomes the core, thus resulting in very slow overall rates.